Toward a Conceptual Data Model Design for the Report Digitalization Project in the CSR Department of PT ABC - Pungus, Stenly; Tumbel, Pauline Ira; Sumual, Gabriel Natalie; Putra, Edson Yahuda; Lontaan, Rolly; Haezer, Hizkia Eben; Medellu, Jonathan (12th International Scholars Conference 2025, 2026)
The increasing demand for digital transformation in the mining sector highlights the importance of developing efficient data management approaches, particularly in Corporate Social Responsibility (CSR) reporting. Current practices in mining companies often rely on conventional spreadsheet-based systems, which lead to inefficiencies such as inconsistent data formats, limited searchability, and difficulties in historical data tracking. This study explores a conceptual approach to data model design that can support the digitalization of CSR reporting in a mining company context, emphasizing efficiency, accuracy, and transparency. Adopting the Design Science Research (DSR) methodology, the study involves problem identification, formulation of solution objectives, and the development of an initial conceptual model using data modeling techniques. Data will be gathered through literature review, interviews, and observation of CSR reporting practices within the mining sector. This work aims to provide an early-stage foundation for future research and system development, offering both theoretical insights into data modeling for CSR digitalization and practical directions for subsequent implementation and evaluation.